Poverty, Welfare and Assessing the Impact of Productive Zakat Distribution - Jumi Herlita; Restu Khaliq (Alhadharah: Jurnal Ilmu Dakwah, 2021)
Zakat is an essential Islamic economic tool to mobilize assets to alleviate poverty and create prosperity. This paper discusses the relationship between zakat, primarily productive zakat, poverty, and welfare from the Islamic perspective. With the potential for extraordinary zakat collection, it is expected that the distribution of zakat will have a tremendous impact on improving the welfare of the mustahik. It is imperative to measure the impact of zakat distribution on mustahik, especially when using appropriate analysis. CIBEST is an analytical tool capable of measuring these impacts from two viewpoints: material and spiritual perspectives. Zakat collection organizations and academics should utilize this analytical tool more to evaluate zakat distribution programs.